2019
DOI: 10.7759/cureus.4768
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Culprit: A Case of Denosumab-induced Hypocalcemia

Abstract: Denosumab is a fully human monoclonal antibody which is used to treat osteoporosis and has been shown to cause hypocalcemia in patients with underlying prostatic and bone malignancies, renal impairment, postmenopausal state, and/or vitamin D deficiency. We present a case of a male patient, with a past medical history negative for the aforementioned conditions, who presented with right shoulder pain and was found to be severely hypocalcemic secondary to denosumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The risk of hypocalcemia following denosumab use for osteoporosis has been demonstrated in multiple case reports and case series for patients with chronic kidney disease [ 7 – 10 ] and in individual case reports for patients with primary sclerosing cholangitis [ 11 ], Crohn's disease [ 8 , 12 , 13 ], and a history of sleeve gastrectomy for marginal gastric ulcers [ 12 ]. A few cases of hypocalcemia with denosumab have been reported in patients with a history of bariatric surgery, but each of these was likely secondary to vitamin D deficiency [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hypocalcemia following denosumab use for osteoporosis has been demonstrated in multiple case reports and case series for patients with chronic kidney disease [ 7 – 10 ] and in individual case reports for patients with primary sclerosing cholangitis [ 11 ], Crohn's disease [ 8 , 12 , 13 ], and a history of sleeve gastrectomy for marginal gastric ulcers [ 12 ]. A few cases of hypocalcemia with denosumab have been reported in patients with a history of bariatric surgery, but each of these was likely secondary to vitamin D deficiency [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…53 Although denosumab treatment has many benefits, a prospective cohort study published in 2016 found that approximately 25.9% of patients treated with denosumab develop persistent hypocalcemia due to its antiresorptive properties. 54 The risk is most severe in patients with chronic kidney disease. To prevent this com plication careful baseline assessment, calcium, and vita min D supplementation if appropriate, and observation, is warranted for all patients treated with denosumab.…”
Section: Antiresorptive Agentsmentioning
confidence: 99%
“…In both patient populations, it has contributed to cases of severe hypocalcemia and hypophosphatemia. While some patients experience severe weakness and tetany, even those with asymptomatic electrolyte abnormalities can display electrocardiogram changes that predispose them to life-threatening cardiac arrhythmias [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case presentations in the literature additionally cite low body mass index, glomerular filtration rate, menopause, bone and prostate malignancies, and vitamin D deficiencies as risk factors that predispose patients to adverse electrolyte imbalances. While a 2016 study demonstrated that a quarter of patients who receive denosumab develop persistent asymptomatic hypocalcemia, [ 8 ] we present the case of a patient with a history of prostate cancer who developed refractory symptomatic severe hypocalcemia, hypophosphatemia, and metabolic acidosis following denosumab.…”
Section: Introductionmentioning
confidence: 99%